THE REPRESENTATION OF SUMBA WOMEN IN THE FILM MARLINA THE MURDERER IN FOUR ACTS (AN ANALYSIS OF CHARLES SANDERS PIERCE) - Aulia Asmarani; Asep Hidayat (Dinasti International Journal of Education Management And Social Science, 2022)
Violence against women is still common in a modern era like today, not least for women who live in the rimland region. Women are often used as a violent objects by men. The patriarchal culture still embraced by some people makes it difficult for women to fight against male domination in their environment. This makes it difficult for women to fight against male domination in their environment. Especially for Sumba women, whose society still adheres to the patriarchal culture. The movie "Marlina, The Murderer in Four Acts" describes the form of resistance of a Sumbanese woman against the injustice that befell her due to men who still lower their self-esteem. This film shows that a woman is not a weak figure; they can fight people who lower their self-esteem with their own hands. This research itself uses qualitative research methods using Charles Sanders Pierce's semiotic analysis in analyzing the data. The result of the analysis of the representation of Sumbanese women in the film "Marlina The Murderer in Four Acts" (1) shows the gender inequality that occurs in Sumba society in the film due to the patriarchy that prevails there, (2) violence and harassment against women and (3) form of women's resistance to the violence and abuse they experience.